Exploring effectiveness of safety information for workplace visitors. (October 2016) - Drupsteen, Linda; Boustras, George
Highlights: The subject is highly relevant in practice but unexplored in safety science. Comparison of objectives of visitor instruction with actual instructions. Data collection in two countries. Shows how safety instructions for visitors could be better focussed. Abstract: Providing safety information to visitors is an important task of each employer, but there is little evidence on what instructions are most effective. This study explores the effectiveness of visitor instructions that are currently in use, by identifying what objectives of visitor instruction are considered most important and assessing whether the actual instructions address these objectives. Data for this study was gathered through a survey that was handed out in a workshop in Cyprus and a workshop in the Netherlands. Focus groups were organised during the workshops, instructions from real companies were handed out and their effectiveness was discussed. The findings from this explorative study show that people expect a visitor instruction to provide information on emergency plans, evacuation routes and on the main risks on the worksite. In this study, the actual visitor instructions only partially matched these expectations. The study showed that in the actual instructions a larger variety of topics was addressed. Strengths and weaknesses of the instructions, according to the participants, mainly relate to the information density and to inclusion of clear, specific information. This finding suggests that the amount of information is very important for the perception of the instruction.